MAPPING AND ACTION PROGRAM DEVELOPMENT FOR BUFFALO IN THE MOUNTAIN REGION - Hasan, Syamsuddin; Aminawar, Muhammad; Darwis, Muhammad; Purnama, Andi (Proceeding Buffalo International Conference, 2013)
Mapping and action programs for buffalo development in the mountain regions of Pinrang regency is particularly important because this zone has the potential in terms of natural resources and human resources that can support development of buffalo in this area. This research was conducted through three approaches, namely integrated approach, participatory approach, and field observations. The analytical tools used were the Location Quotient (LC) and SWOT analysis. Data sources were secondary data, supporting documents, interviews, direct observations, and focus group discussion (FDG). Mapping development of buffalo in the mountain areas of Pinrang has a comparative advantage compared to cattle and goats. Action development programs of Buffalo were divided into nine action programs, namely (1) Restructuring of the region by breeding center development, (2) Improvement of buffalo production and productivity, (3) Prevention and Control of buffalo diseases, (4) Improvement of forage production, (5) Improvement of livestock technology application, (6) Improvement of livestock marketing and animal husbandry production, (7) Institutional strengthening of the farmer group, (8) Improvement of human resources capacity as the actors of livestock activities, (9) Regulations and implementation of programs to support investment for buffalo Â livestock